2018
DOI: 10.1016/j.polymer.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight, branching and temperature on dynamics of polypropylene melts at very high shear rates

Abstract: Dynamics of linear polypropylene (L-PP) and long-chain branched polypropylene (LCB-PP) miscible blends, having weight average molecular weight between 64-78 kg/mol, was investigated via high shear rate rheology. Results obtained were compared with the corresponding data for L-PP. Highshear rate secondary Newtonian plateaus, , were identified at three different temperatures for well entangled L-PP/LCB-PP blends above shear rates of 2 • 10 6 1/s and their dependence on weight average molecular weight, Mw, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…GPC is one of the most important methods to determine the MMD of polymers [63]. GPC measurement, a well-established concept in the literature, provides a further possibility to determine the molecular structure and any modifications made to polymers [51,[64][65][66][67][68].…”
Section: Molar Mass Determinationmentioning
confidence: 99%
“…GPC is one of the most important methods to determine the MMD of polymers [63]. GPC measurement, a well-established concept in the literature, provides a further possibility to determine the molecular structure and any modifications made to polymers [51,[64][65][66][67][68].…”
Section: Molar Mass Determinationmentioning
confidence: 99%
“…Rheology measurements have been shown in literature to be a good tool of identifying molecular structures and to be very sensitive to changes in them [ 36 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Several studies have investigated the rheological behavior of blends with linear PP and branched PP or PE and have shown that these blends have a higher shear thinning effect or strain hardening compared to linear PP [ 47 , 48 , 49 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyolefin, mostly low‐density polyethylene (PE‐LD), high‐density polyethylene (PE‐HD) and polypropylene (PP), are among the most widely used and produced polymeric materials in the world. They are used in different industry sectors for example packaging, food industry, biomedical applications, films, bags 1–4 . The operating life from most of these polyolefin products are lower than 1 month 5,6 .…”
Section: Introductionmentioning
confidence: 99%